Promoting Safe and Legal Migration: Awareness Generation Among Students in Jalandhar District. - Sahai, Paramjit S. and Chand, Krishan (2012)
International migration has received a big boost with the fast development of means of communication and transportation. Punjab is one of the most prominent states in India with respect to global migration, since many migrate overseas for various regions. A survey based study was carried out, during the road shows organised by CRRID in Jalandhar district for the promotion of safe and legal migration. A questionnaire was circulated to the students of schools and colleges to elicit their perception as they are the potential candidates for migration. This paper examines data collected from them and draws necessary conclusions.